Cultivo de camarão marinho (Penaeus vannamei) e de plantas halófitas (Batis marítimas, Salicornia neei e Sesuvium portulacastrum), em sistema aquapônico, com variação de salinidade na estação chuvosa - Marques, Larissa Liberalino (2023)
Aquaculture is growing faster than other major food production sectors. Shrimp farming is an important aquaculture segment, with the cultivation of marine shrimp Penaeus vannamei contributing to 52.9% of crustacean production in the world. The objective of this work was to study the influence and use of nutrients from the water of the cultivation of shrimp Penaeus vannamei, by the plants Batis maritimes, Salicornia neei and Sesuvium portulacastrum, aiming at their production in aquaponic system, during the rainy season. For this purpose, 208 P. vannamei Shrimp weighing 1.2 g were cultivated in 53-liter boxes (16 boxes; 13 animals/box), in an aquaponics system with three types of halophyte plants, or without the plants, for 55 days at the time rainy. Four treatments were performed, with four replications: salinity 5‰ with and without plants; 25‰ with and without plants. Water quality was evaluated, as well as plant growth and shrimp zootechnical indices. In the present work, the average oxygen concentration in the culture tanks was 5.32 ± 0.26 mg.L-1. Taking into account the two salinity levels, 5‰ and 25‰, in a study the presence of the aquaponic system did not affect the concentration of dissolved oxygen in the water. Therefore, the pH, salinity and oxygen parameters did not present significant differences when presented within the same salinity in the 5‰ case, only the pH and temperature parameters suffered an influence on the salinity of 25‰. The halophyte plants of the present study were analyzed, evaluating the growth of all of them within the same salinity, in the case 5‰, thus presenting a significant difference (p≤0.05), with a greater growth observed for the species S. portulacastrum, with an average of 21.6 cm, followed by B. maritime and S. neei, the latter showed the lowest growth. Shrimp showed greater survival in tanks with a higher salinity of 25‰ without the presence of plants (57.15%; p≤0.05), but the highest final biomass was found in salinity of 25‰ in association with plants (713, 39 g.m3; p≤0.05). In the experimental conditions of this work, it is concluded that the use of aquaponics with P. vannamei cultivation water is efficient for the production of the three halophyte plants (S. portulacastrum, S. neei and B. maritime), being especially indicated the salinity 25‰ for the production of the species S. portulacastrum, and at this salinity with association of plants it is also efficient for the production of P.vannamei.